2017
DOI: 10.1111/faf.12200
|View full text |Cite
|
Sign up to set email alerts
|

Improving estimates of population status and trend with superensemble models

Abstract: Fishery managers must often reconcile conflicting estimates of population status and trend. Superensemble models, commonly used in climate and weather forecasting, may provide an effective solution. This approach uses predictions from multiple models as covariates in an additional “superensemble” model fitted to known data. We evaluated the potential for ensemble averages and superensemble models (ensemble methods) to improve estimates of population status and trend for fisheries. We fit four widely applicable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
109
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(112 citation statements)
references
References 54 publications
(72 reference statements)
2
109
1
Order By: Relevance
“…This would allow researchers to link management decision theory to the likely population dynamics for all species worldwide. Ensemble modelling : Stock assessment will generally be more robust if management advice is based on an ensemble of alternative life‐history assumptions (Stewart & Martell, ). Results from a model ensemble can be presented using a decision table (Hilborn, Pikitch, & Francis, ) or via ensemble weighting of model results (Anderson et al, ), but either presentation requires some objective method for determining the weight of different unknown “states of nature.” I therefore recommend that stock assessments increasingly present results using an ensemble of life‐history values, where model weights can be obtained from the multivariate distribution for these parameters. Strategic decisions : Finally, strategic decision‐making in ecosystem‐based management is increasingly informed by models that include dynamics for multiple species and physical drivers (Fulton et al, ). For example, ecosystem models have been used to forecast likely impacts of ocean acidification, temperature changes or invasive species on fisheries potential (Cheung, Lam, & Pauly, ; Marshall et al, ; Morello et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This would allow researchers to link management decision theory to the likely population dynamics for all species worldwide. Ensemble modelling : Stock assessment will generally be more robust if management advice is based on an ensemble of alternative life‐history assumptions (Stewart & Martell, ). Results from a model ensemble can be presented using a decision table (Hilborn, Pikitch, & Francis, ) or via ensemble weighting of model results (Anderson et al, ), but either presentation requires some objective method for determining the weight of different unknown “states of nature.” I therefore recommend that stock assessments increasingly present results using an ensemble of life‐history values, where model weights can be obtained from the multivariate distribution for these parameters. Strategic decisions : Finally, strategic decision‐making in ecosystem‐based management is increasingly informed by models that include dynamics for multiple species and physical drivers (Fulton et al, ). For example, ecosystem models have been used to forecast likely impacts of ocean acidification, temperature changes or invasive species on fisheries potential (Cheung, Lam, & Pauly, ; Marshall et al, ; Morello et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are sufficient data to conduct retrospective skill testing over seasonal or short‐term forecasts, there is surprisingly little research using skill testing to compare performance among alternative models. I therefore recommend skill testing to either identify which models to use for different planning horizons, or how to weight predictions from multiple models when using an ensemble model for forecasting (e.g., Anderson et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous analyses showed that a random forest superensemble consistently had the best or among the best performance characteristics when compared to other possible superensemble regression models (Anderson et al . ). The superensemble outperformed the individual models in cross‐validation on simulated data with, for example, a median absolute proportional error in B/B MSY of 0.32 compared to 0.42–0.56 for the individual models (Anderson et al .…”
Section: Methodsmentioning
confidence: 97%
“…The superensemble outperformed the individual models in cross‐validation on simulated data with, for example, a median absolute proportional error in B/B MSY of 0.32 compared to 0.42–0.56 for the individual models (Anderson et al . ).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation